(untitled) (Journal of Economic Research & Business Administration, 2019)
Economic fluctuations are changing the business environment. The number of firms that want to audit their financial statements fell sharply after the 2008 crisis, which is the reason for the reduction in the cost of audit services, tough competition in the market. The audit report indirectly affects the prestige and attractiveness of companies in the eyes of external users. Audited firms begin to doubt whether such a change in price has affected the quality of the audit. Based on the regression analysis, the article examines the possible audit quality change in the face of falling audit costs. The factors, which can influence on audit quality, are audit fee, auditor qualification, additional services, explanatory paragraphs, type of audit report, period of the audit and the size of the audited company. EBITDA reflects the audit quality. The results showed that the reduction in fees is not a factor affecting the quality of the audit service.